Asuhan Akupunktur Pada Kasus Nyeri Punggung Bawah dengan Sindrom Stagnasi Qi dan Xue di Geriya Sehat Bali Dwipa Husada - I Made Peri Budiawan; Puspo Wardoyo; Leny Candra; Amal Prihatono (Universitas Respati Indonesia, 2026)
Low back pain is one of the most common musculoskeletal complaints and can reduce functional ability and quality of life. The management of low back pain generally involves pharmacological therapy; however, long-term use may cause adverse effects. Therefore, non-pharmacological therapies are needed as safer and more holistic alternatives, one of which is acupuncture. This study aimed to describe acupuncture care in a case of low back pain with Qi and Blood Stagnation Syndrome. This research used a qualitative approach with a case study design. The participant was a 67-year-old woman who complained of low back pain radiating to the buttocks. The study was conducted at Geriya Sehat Bali Dwipa Husada, where acupuncture therapy was administered in six sessions. Data were collected using the Four Diagnostic Methods of acupuncture, including observation (Wang), listening and smelling (Wen), inquiry (Wen), and palpation (Qie), supported by documentation studies.The results showed a gradual improvement in the client’s condition, indicated by a reduction in pain intensity based on the Numeric Rating Scale (NRS), decreased stiffness, and improved ability to perform daily activities.It can be concluded that acupuncture care helps reduce low back pain in cases of Qi and Blood Stagnation Syndrome and can be used as a complementary therapy.